Severe anaphylaxis caused by intravenous anti‐cancer drugs. (10th September 2021) - Horita, Nobuyuki; Miyagi, Etsuko; Mizushima, Taichi; Hagihara, Maki; Hata, Chiaki; Hattori, Yuki; Hayashi, Narihiko; Irie, Kuniyasu; Ishikawa, Hideyuki; Kawabata, Yusuke; Kitani, Yosuke; Kobayashi, Noritoshi; et al.
Abstract: Background: The incidence and risk factors of severe anaphylaxis by intravenous anti‐cancer drugs are unclear, whereas those of milder reactions have been reported. Study Design: Electronic medical charts of cancer patients who have undergone intravenous chemotherapy between January 2013 and October 2020 in a university hospital were retrospectively reviewed. Non‐epithelial malignancies were also included in the analysis. "Severe anaphylaxis" was judged using Brown's criteria: typical presentation of anaphylaxis and one or more of hypoxia, shock, and neurologic compromise. (UMIN000042887). Results: Among 5584 patients (2964 males [53.1%], 2620 females [46.9%], median age 66 years), 88, 200 person‐day anti‐cancer drug administrations were performed intravenously, and 27 severe anaphylaxes were observed. The causative drugs included carboplatin (14 cases), paclitaxel (9 cases), and cisplatin, docetaxel, trastuzumab, and cetuximab (1 case each). The person‐based lifetime incidence of severe anaphylaxis for patients who received at least one intravenous chemotherapy was 0.48% (27/5584, 95% confidence interval (CI) 0.30%–0.67%) and the administration‐based incidence was 0.031% (27/88, 200, 95% CI 0.019%–0.043%). Among 124 patients who received at least 10 carboplatin administrations, 10 patients experienced carboplatin‐induced severe anaphylaxis (10/124, 8.1%, 95% CI 3.0%–13.1%). Carboplatin caused severe anaphylaxis after at least 9‐min interval since the drip started. Thirteen out of 14 patients experienced carboplatin‐induced severe anaphylaxis within a 75‐day interval from the previous treatment. Paclitaxel infusion caused severe anaphylaxis after a median of 5 min after the first drip of the day at a life‐long incidence of 0.93% (9/968, 95% CI 0.27%–1.59%). Conclusion: We elucidated the high‐risk settings of chemotherapy‐induced severe anaphylaxis. Abstract : 88, 200 person‐days of chemotherapy provided for 5584 patients were reviewed. They induced 27 severe anaphylaxes defined by Brown's criteria. Most were caused by carboplatin (14 cases) or paclitaxel (9 cases).